(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses the role and significance of didactic games in teaching a foreign language and effective communication. The didactic game allows you to solve many pedagogical tasks in the game style that is most convenient and attractive for students.